Tracking, Synthesizing, and Sharing Global Batrachochytrium Data at AmphibianDisease.org - Koo, Michelle S.; Vredenburg, Vance T.; Deck, John B.; Olson, Deanna H.; Ronnenberg, Kathryn L.; Wake, David B. (Frontiers in Veterinary Science, 2021)
Emerging infectious diseases have been especially devastating to amphibians, the most endangered class of vertebrates. For amphibians, the most impactful disease is chytridiomycosis, caused by one of two chytridiomycete fungal pathogens Batrachochytrium dendrobatidis (Bd) and Batrachochytrium salamandrivorans (Bsal). Research over the last two decades has shown that susceptibility to this disease varies greatly with respect to a suite of host and pathogen factors such as phylogeny, geography (including abiotic factors), host community composition, and historical exposure to pathogens; yet, despite a growing body of research, a comprehensive understanding of global chytridiomycosis incidence remains elusive. In a large collaborative effort, Bd-Maps was launched in 2007 to increase multidisciplinary investigations and understanding using compiled global Bd occurrence data (Bsal was not discovered until 2013). As its database functions aged and became unsustainable, we sought to address critical needs utilizing new technologies to meet the challenges of aggregating data to facilitate research on both Bd and Bsal. Here, we introduce an advanced central online repository to archive, aggregate, and share Bd and Bsal data collected from around the world. The Amphibian Disease Portal (https://amphibiandisease.org) addresses several critical community needs while also helping to build basic biological knowledge of chytridiomycosis. This portal could be useful for other amphibian diseases and could also be replicated for uses with other wildlife diseases. We show how the Amphibian Disease Portal provides: 1) a new repository for the legacy Bd-Maps data; 2) a repository for sample-level data to archive datasets and host published data with permanent DOIs; 3) a flexible framework to adapt to advances in field, laboratory and informatics technologies; and 4) a global aggregation of Bd and Bsal infection data to enable and accelerate research and conservation. The new framework for this project is built using biodiversity informatics best practices and metadata standards to ensure scientific reproducibility and linkages across other biological and biodiversity repositories.